Assessment of greenhouse gas emissions into the atmosphere from the northern peatlands using the Wetland-DNDC simulation model: A case study of the Great Vasyugan Mire, Western Siberia - Mikhalchuk, Alexander; Borilo, Lyudmila P.; Burnashova, Elena; Kharanzhevskaya, Yulia A.; Akerman, Ekaterina A.; Chistyakova, Natalia; Kirpotin, Sergey N. 1964-; Pokrovsky, Oleg S.; Vorobyev, Sergey N. биолог (Atmosphere)
The peatlands of Western Siberia occupy an area of about 1 million km2 and act as important regulator of carbon exchange between the earth and the atmosphere. Extrapolation of the results of discrete field measurements of CO2 fluxes in bog ecosystems to such a territory is a difficult task, and one of the ways to overcome it is to use a simulation model such as DNDC. However, using this model with a specific territory requires ground verification to confirm its effectiveness. Here, we tested the DNDC model on the largest pristine bog ecosystem of the world, the Great Vasyugan Mire (GVM). The GVM of western Siberia is virtually undisturbed by anthropogenic activity and is the largest bog of Northern Eurasia (53,000 km2). Based on various ground-based observations, the performance of the Wetland-DNDC model was demonstrated (Thale coefficient 0.085 and R2 = 0.675 for CO2). Model input parameters specific to the GVM were constrained and model sensitivity to a wide range of input parameters was analyzed. The estimated annual terrestrial carbon fluxes in 2019 from the GVM test site are mainly controlled by plant respiration (61%) and forest floor degradation (38%). The net CO2 emission flux was 8600 kg C ha−1 year−1, which is in line with estimates from other independent studies.